Diagnostic Indices of Intraoperative Gross Assessment in the Surgical Staging of Endometrial Cancer - Chaiprasit, Bundaree; Chirdchim, Watcharin (Thai Journal of Obstetrics and Gynaecology, 2021)
Objectives: To determine the diagnostic indices of intraoperative gross assessment in the surgical staging of endometrial cancer. Materials and Methods: We retrospectively reviewed medical records and operative notes of a total of 112 patients who were diagnosed with endometrial cancer in Prapokklao Hospital between 2014 and 2019. We aimed to determine the diagnostic indices of gross visual inspection compared with the final pathological reports. Diagnostic indices included sensitivity, specificity, negative predictive value, positive predictive value, and likelihood ratio with a 95% confidence interval. Specimen evaluation sites consisted of five parameters including cervical involvement, adnexal involvement, myometrial invasion, tumor diameter, and lymph node involvement. Results: Intraoperative gross assessment showed good accuracy in all parameters, ranging from 71.1% to 89.9%, while tumor diameter showed the best accuracy (89.9%). Cervical involvement, adnexal involvement and myometrial invasion showed relatively poor sensitivity (46.7%, 18.8%, 56.6%) but good specificity (95.6%, 95.5%, 90.9%). For para-aortic lymph node involvement, the number of samples was too limited to assess the diagnostic performance. Conclusion: Gross intraoperative assessment in surgical staging had good specificity and accuracy but poor sensitivity. The results implied that gross intraoperative assessment was an applicable tool. However, more modality and intervention should be combined in order to help in deciding the best surgical treatment for each individual.